The rise of a network: Spillover of political patronage and cronyism to the private sector - Moon, Terry; Schoenherr, David (Journal of Financial Economics, 2022)
We document that networks that gain access to political power and use it for patronage appointments also gain control over resource allocation in the private sector. Specifically, following a presidential election in Korea, the president appoints members of his network into important positions in government, and private banks respond by appointing executives from the same network to establish links to the administration. Consequently, firms linked to the network obtain more credit at a lower rate from government and private banks alike, despite higher default rates. Micro-level data on loans and variation in network links for the same firm across lenders over time sharpen the interpretation of our results. In a parsimonious model, we show that efficiency costs are higher when government and private banks are controlled by the same group rather than different groups: in-group firms invest in more unprofitable projects, whereas out-group firms lack funding for highly profitable investments.